Further evidence for LBP-1c/CP2/LSF association in Alzheimer's disease families. Issue 11 (4th November 2005) - Bertram, L; Parkinson, M; McQueen, M B; Mullin, K; Hsiao, M; Menon, R; Moscarillo, T J; Blacker, D; Tanzi, R E
Abstract : Objectives: Several studies suggested chromosome 12 harbours an Alzheimer's disease (AD) risk factor gene. Significant association of a single nucleotide polymorphism (SNP) in the 3′ UTR of transcription factor CP2 ( LBP-1c/CP2/LSF or TFCP2 ) at 12q13 was reported in three independent case-control studies, but no family based analyses have been performed to date. Methods: Genotypes for three SNPs were generated in two independent AD family samples. A meta-analysis on all published case-control studies was also performed. Results: The A allele of the 3′ UTR SNP was associated with increased risk for AD in one sample (odds ratio (OR) 2.1, 95% confidence interval (95% CI) 1.1 to 4.3), but not in the other, possibly due to low power. Haplotype analyses showed that this allele is part of a putative risk-haplotype overtransmitted to affected individuals in one sample and in both samples combined. Meta-analysis of the previously associated 3′ UTR SNP showed a trend towards a protective effect of the A allele in AD (OR 0.73, 95% CI 0.5 to 1.1). Conclusions: This is the first study to examine LBP-1c/CP2/LSF in AD families, and the fifth to independently show significant association. While our results support a role of this gene in AD pathogenesis, the direction of the effect remains uncertain, possibly indicating linkage disequilibrium with another variant nearby.